Lutein administration during gestation protects morphine withdrawal-induced on reflexive motor behavior in mice offspring's - Sahand Sariaslani; Shahin Hassanpour; Bita Vazir (Heliyon)
Exposure to morphine during gestation period has vital effect on infants’ neurodevelopmental growth pattern. Lutein shows protective qualities regarding neurodegeneration and the development of the brain. This study aimed to investigate effect of parental exposure to lutein on adverse effect of the morphine withdrawal syndrome on reflexive motor behavior in mice offspring. Fourteen male mice and 56 adult female mice were randomly assigned to seven groups: the control group containing male and female mice that refrained from morphine; group 2 was morphine-abstinent male mice and female mice with no prior drug exposure; group 3 including morphine-abstinent female mice and male mice without drug experience; and group 4 of drug-naïve male and female mice. Groups 5–7 were similar to groups 2–4, but drug-naïve subjects received injections of lutein (10 mg/kg). Following delivery, offspring from each group were chosen to assess behavior and reflexive motor behaviors. Also, blood samples were collected to measure serum antioxidant activity. Based on the findings, reflexive motor behaviors significantly decreased following prenatal exposure to morphine (P < 0.05), however, no significant difference was seen between morphine exposed male with male and female morphine exposed mice (P > 0.05). Lutein administration had no effect on reflexive motor behaviors in male morphine exposed group (P > 0.05) but lutein administration significantly decreased adverse effect of the morphine on reflexive motor behaviors in female exposed group (P < 0.05). No significant difference was seen between male and females received morphine (P > 0.05). Lutein administration decreased serum malondialdehyde (MDA) production and increased superoxide dismutase (SOD), glutathione peroxidase (GPx) and total antioxidant status (TAS) levels in morphine exposed mice. It seems, maternal exposure to lutein had protective role on adverse effect of the morphine on reflexive motor behaviors in offspring.